Titanium-based composite material resistant to high temperature of 750 DEG C and short-process preparation method thereof
By introducing nanospherical silicides and high-even-to-diameter fiber-like TiBw reinforced phases into titanium-based composites, and adopting a specific heat treatment process, the problem of the reduction in strength of traditional high-temperature titanium alloys at high temperatures is solved, and excellent mechanical properties at high temperatures of 750°C are achieved.
Patent Information
- Application Number
- CN202411742125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The strength of traditional high-temperature titanium alloys is greatly reduced at high temperatures, making it difficult to meet the needs of complex high-temperature working conditions. At the same time, the addition of reinforcement phases in the titanium alloy matrix has problems that enhancement contribution is closely related to its own aspect ratio.
By introducing nanospherical silicide and high-even-to-diameter fiber-like TiBw reinforced phase, and using open forging, solution quenching and multi-pass drawing process, the precipitation and size of silicides are regulated to ensure the aspect ratio of fibrous TiBw.
The fiber-like TiBw enhancement with fine grains of the matrix, uniform distribution of spherical silicides and high aspect ratio is achieved, which significantly improves the normal high temperature mechanical properties of titanium-based composites and is suitable for high temperature environments of 750℃.
Smart Images

Figure CN119553136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy preparation, and in particular to a 750°C high-temperature resistant titanium-based composite material and a short-process preparation method thereof. Background Art
[0002] High-temperature titanium alloys have the characteristics of low density, high specific strength, corrosion resistance and high temperature resistance, and are widely used in the aerospace field. However, with the development of the aerospace industry, the requirements for the service temperature and comprehensive mechanical properties of high-temperature titanium alloys are getting higher and higher, and traditional high-temperature titanium alloys are difficult to meet the needs. Therefore, it is particularly important to break through the 600℃ "thermal barrier" temperature and develop high-temperature titanium-based materials of 650-700℃ or even 750℃ suitable for the aerospace field.
[0003] Research has found that the equiaxed structure of high-temperature titanium alloys has excellent room temperature performance, but the grain boundaries soften at high temperatures, and its high temperature strength is greatly reduced, making it difficult to meet the needs of complex working conditions such as high temperatures; furthermore, although the dual-state structure has high strength at high temperatures, its room temperature strength and plasticity are both average. Therefore, titanium alloys need to select a suitable matrix structure to simultaneously meet their performance requirements at room temperature and high temperatures; in addition, adding a reinforcing phase to the titanium alloy matrix can improve high temperature strength and creep resistance, thereby increasing its use temperature; for example, composite material strengthening methods are generally considered to be a method that can effectively improve material strength, stiffness and hardness, and to a certain extent maintain the inherent plasticity of the metal matrix; as a hard short fiber particle, TiBw is significantly different from other particle-shaped reinforcements, and usually plays a strengthening role in the form of load transfer. Based on this, the development of titanium-based composite materials with a new near-α-type Ti-Al-Sn-Zr-Mo-Si high-temperature titanium alloy as the matrix has attracted much attention from researchers. However, its strengthening contribution is closely related to its own aspect ratio. Large plastic deformation methods such as rolling, extrusion, and die forging will seriously damage the aspect ratio of TiBw, greatly weakening its load transfer capacity. In addition, the in-situ self-generated silicide particles in the Ti-Al-Sn-Zr-Mo-Si titanium alloy are used to improve the material properties, but silicides also have the problem of easy coarsening and growth, resulting in reduced plasticity. Therefore, obtaining TiBw with small silicide size, uniform distribution, and high aspect ratio is the key to preparing titanium-based composite materials resistant to 750°C high temperature. Summary of the invention
[0004] Based on the above purpose, the present invention provides a 750°C high temperature resistant titanium-based composite material and a short-process preparation method thereof.
[0005] A titanium-based composite material resistant to high temperatures of 750°C, comprising aluminum, tin, zirconium, molybdenum, niobium, tungsten, silicon, boron and titanium; wherein the mass percentage of each component is:
[0006] Aluminum: 5% to 8%;
[0007] Tin: 3% to 6%;
[0008] Zirconium: 5% to 8%;
[0009] Molybdenum: 1.5% to 2.5%;
[0010] Niobium: 1.5% to 2.5%;
[0011] Tungsten: 0.5% to 1.5%;
[0012] Silicon: 0.2% to 0.5%;
[0013] Boron: 0.1% to 0.5%;
[0014] The balance is titanium and unavoidable impurities.
[0015] Optionally, the titanium is selected from titanium sponge with a purity of not less than 99.5%; the zirconium is selected from zirconium sponge with a purity of not less than 99.5%; and the purity of aluminum, tin, molybdenum, niobium and tungsten is not less than 99.9%.
[0016] Optionally, the purity of the silicon is not less than 99.9%, and its particle size is controlled at 1 to 5 microns; the purity of the boron is not less than 99.9%, and its particle size is 1 to 5 microns.
[0017] A short-process preparation method for a 750°C high-temperature resistant titanium-based composite material comprises the following steps:
[0018] S1: weighing the raw materials constituting the titanium-based composite material according to weight percentage, including titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder;
[0019] S2: after the raw materials are uniformly mixed, they are placed in a vacuum induction suspension melting furnace and smelted under vacuum conditions to obtain an alloy ingot;
[0020] S3: After heating, the titanium-based alloy ingot is subjected to heat preservation treatment, and then forging is performed in sequence along three directions, namely, X, Y, and Z, so that the ingot undergoes plastic deformation to form a titanium-based composite material of a predetermined shape;
[0021] S4: subjecting the titanium-based composite material after blank forging to a solid solution treatment at a set temperature, and after heat preservation, placing it in salt water for quenching and cooling;
[0022] S5: The titanium-based composite material after the solution treatment is heated again to a set temperature and kept warm, and then multiple stretchings are performed along the X and Y directions to obtain a finished titanium-based composite material resistant to high temperatures of 750°C.
[0023] Optionally, the S2 specifically includes:
[0024] S21: adding weighed titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder into a mixing device in proportion, mixing for 20 to 30 minutes, and mixing evenly to form a mixture A;
[0025] S22: placing the mixture A in a smelting chamber of a vacuum induction suspension furnace, and evacuating the smelting chamber to 3×10-3Pa before smelting;
[0026] S23: introducing argon gas under vacuum conditions until the pressure reaches 100 Pa, raising the melting temperature to 1900-2000° C., maintaining the melting for 10-20 minutes, and repeating the melting 3-5 times;
[0027] S24: After smelting, pour the alloy liquid into a steel mold preheated to 200-300°C, and cool to room temperature along with the furnace to obtain an alloy ingot.
[0028] Optionally, the S3 specifically includes:
[0029] S31: heating the alloy ingot to a temperature 100 to 150° C. higher than the β phase transformation point, and keeping the temperature for 30 to 60 minutes;
[0030] S32: After the heat preservation is completed, the ingot is forged in three directions, X, Y and Z, forging 1 to 3 times, with a deformation amount of 50%;
[0031] S33: After the multi-directional forging is completed, a titanium-based composite material of a predetermined shape is obtained.
[0032] Optionally, the S4 specifically includes:
[0033] S41: heating the titanium-based composite material after blank forging to a β-phase temperature of 1200-1250° C., and keeping the temperature for 1-2 hours;
[0034] S42: After the heat preservation is completed, the titanium-based composite material is quickly moved into a 20-25% by mass salt solution for quenching and cooling to room temperature.
[0035] Optionally, the S5 specifically includes:
[0036] S51: heating the solution treated titanium-based composite material to a temperature 100 to 150° C. higher than the β phase transition point, and keeping the temperature for 30 to 60 minutes;
[0037] S52: After the heat preservation is completed, 1 to 4 stretching passes are performed along the X and Y directions respectively, and the deformation amount each time is 10 to 30%;
[0038] S53: After the drawing is completed, the product is cooled to room temperature to obtain a finished product of a titanium-based composite material resistant to high temperature of 750°C.
[0039] Beneficial effects of the present invention:
[0040] The invention introduces nano-spherical silicide and high aspect ratio fibrous TiBw reinforcement phase, so that the alloy has excellent normal high temperature mechanical properties, and obtains a 750°C high temperature resistant titanium-based composite material with fine matrix grains, uniform distribution of spherical silicide and high aspect ratio fibrous TiBw reinforcement.
[0041] The present invention realizes reasonable regulation of the precipitation and size of silicides and ensures the aspect ratio of the fibrous TiBw reinforcement phase through the combination of blanking forging, solution quenching treatment and multi-pass drawing process, thereby obtaining a titanium-based composite material resistant to high temperatures of 750°C.
[0042] The present invention combines blanking forging, solution quenching treatment and multi-pass drawing process, and has a mature preparation process, which can realize effective control of process parameters in the preparation link, and the prepared material has uniform structure, which significantly improves the performance stability of titanium-based composite materials used as structural materials.
[0043] The prepared 750°C high temperature resistant titanium-based composite material has a room temperature tensile strength of 1200-1400 MPa and an elongation of 5-10%, a 650°C tensile strength of 750-850 MPa and an elongation of 20-50%, a 700°C tensile strength of 650-750 MPa and an elongation of 50-80%, and a 750°C tensile strength of 550-650 MPa and an elongation of 100-150%. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 A schematic diagram of a short-process preparation method according to an embodiment of the present invention;
[0046] Figure 2 A schematic diagram of the as-cast microstructure of an embodiment of the present invention;
[0047] Figure 3 Schematic diagram of a normal high temperature stretching curve of an embodiment of the present invention. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0049] It should be noted that the references to "one embodiment", "an embodiment", "an exemplary embodiment", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).
[0050] In general, a term can be understood, at least in part, from its use in context. For example, depending, at least in part, on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular sense, or can be used to describe a combination of features, structures, or characteristics in the plural sense. Additionally, the term "based on" can be understood as not necessarily intended to convey an exclusive set of factors, but can instead, depending, at least in part, on the context, allow for the presence of other factors that are not necessarily explicitly described.
[0051] Example 1
[0052] like Figure 1-Figure 3 As shown, a titanium-based composite material resistant to high temperatures of 750°C includes aluminum, tin, zirconium, molybdenum, niobium, tungsten, silicon, boron and titanium; wherein the mass percentage of each component is,
[0053] Aluminum (Al): 6.5%;
[0054] Tin (Sn): 4%;
[0055] Zirconium (Zr): 6%;
[0056] Molybdenum (Mo): 2%;
[0057] Niobium (Nb): 2%;
[0058] Tungsten (W): 1%;
[0059] Silicon (Si): 0.4%;
[0060] Boron (B): 0.2%;
[0061] The balance is titanium (Ti) and inevitable impurities.
[0062] Titanium is selected from titanium sponge with a purity of not less than 99.5%; zirconium is selected from zirconium sponge with a purity of not less than 99.5%; the purity of aluminum, tin, molybdenum, niobium and tungsten is not less than 99.9%.
[0063] The purity of silicon is not less than 99.9%, and its particle size is controlled at 3 microns; the purity of boron is not less than 99.9%, and its particle size is 3 microns.
[0064] A short-process preparation method for a 750°C high-temperature resistant titanium-based composite material comprises the following steps:
[0065] S1: weighing the raw materials constituting the titanium-based composite material according to weight percentage, including titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder;
[0066] S2: After the raw materials are uniformly mixed, they are placed in a vacuum induction suspension furnace and smelted under vacuum conditions to obtain an alloy ingot;
[0067] S3: After heating, the titanium-based alloy ingot is subjected to heat preservation treatment, and then forging is performed in sequence along three directions, namely, X, Y, and Z, so that the ingot undergoes plastic deformation to form a titanium-based composite material of a predetermined shape;
[0068] S4: subjecting the titanium-based composite material after blank forging to a solid solution treatment at a set temperature, and after heat preservation, placing it in salt water for quenching and cooling;
[0069] S5: The titanium-based composite material after the solution treatment is heated again to a set temperature and kept warm, and then multiple stretchings are performed along the X and Y directions to obtain a finished titanium-based composite material resistant to high temperatures of 750°C.
[0070] S2 specifically includes:
[0071] S21: adding weighed titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder into a mixing device in proportion, mixing for 25 minutes, and mixing evenly to form a mixture A;
[0072] S22: placing the mixture A in a smelting chamber of a vacuum induction suspension furnace, and evacuating the smelting chamber to 3×10-3Pa before smelting;
[0073] S23: introducing argon gas under vacuum conditions until the pressure is 100 Pa, raising the melting temperature to 1950° C., maintaining the melting for 15 minutes, and repeating the melting 4 times;
[0074] S24: After smelting, pour the alloy liquid into a steel mold preheated to 250°C, and cool to room temperature along with the furnace to obtain an alloy ingot.
[0075] S3 specifically includes:
[0076] S31: heating the alloy ingot to a temperature 130° C. higher than the β phase transformation point, and keeping the temperature for 45 minutes;
[0077] S32: After the heat preservation is completed, the ingot is forged in the three directions of X, Y and Z in sequence, forging 1 to 3 times (the three directions of X, Y and Z are counted as one time), and the deformation amount is 50%;
[0078] S33: After the multi-directional forging is completed, a titanium-based composite material of a predetermined shape is obtained.
[0079] S4 specifically includes:
[0080] S41: heating the titanium-based composite material after the blank forging to a β phase temperature of 1230° C. and keeping the temperature for 1.5 hours;
[0081] S42: After the heat preservation is completed, the titanium-based composite material is quickly moved into a 23% by mass salt solution for quenching and cooling to room temperature.
[0082] S5 specifically includes:
[0083] S51: heating the solution treated titanium-based composite material to a temperature 130° C. higher than the β phase transition point, and keeping the temperature for 45 minutes;
[0084] S52: After the heat preservation is completed, three stretching passes are performed along the X and Y directions respectively (the X and Y directions are counted as one pass), and the deformation amount of each stretching is 20%;
[0085] S53: After the drawing is completed, the product is cooled to room temperature to obtain a finished product of a titanium-based composite material resistant to high temperature of 750°C.
[0086] The titanium-based composite material prepared in Example 1 has a phase composition of alternating arrangement of lamellar α-Ti and β-Ti, precipitation of nano-spherical silicides at grain boundaries, and fibrous TiBw with a high aspect ratio; the width of the lamellar α-Ti phase is 0.1 μm, the nano-scale spherical silicides are evenly distributed with a size of 50 to 300 nm, and the aspect ratio of the fibrous TiBw is 17:1; the room temperature tensile strength of the titanium-based composite material is 1270.74 MPa, and the elongation is 6.44%, the tensile strength at 650°C is 856.13 MPa, and the elongation is 30.6%, the tensile strength at 700°C is 721.16 MPa, and the elongation is 41.5%, and the tensile strength at 750°C is 589.73 MPa, and the elongation is 64.4%.
[0087] Example 2
[0088] A 750°C high temperature resistant titanium-based composite material is composed of the following components by weight percentage: 5% Al, 3% Sn, 5% Zr, 1.5% Mo, 1.5% Nb, 0.5% W, 0.2% Si (particle size controlled at 1 micron), 0.1% B (particle size controlled at 1 micron), and the balance is Ti and unavoidable impurities.
[0089] The short process preparation method is as follows:
[0090] S1: Weigh each raw material according to the weight percentage of each component;
[0091] S2: Sponge titanium, high-purity aluminum, sponge zirconium, high-purity tin ingots, Al-Mo alloy, Al-Nb alloy, Al-W alloy, pure Si powder and pure B powder are mixed for 20 minutes and added into a vacuum induction suspension furnace. Before smelting, the smelting chamber needs to be evacuated to a vacuum degree of 3×10-3Pa, and then argon gas is introduced with a gas pressure of 100Pa. Then, the smelting is performed at 1900°C, and the average holding time after smelting is 15 minutes. The smelting is repeated 3 times. After the smelting is completed, the alloy liquid needs to be poured into a steel mold preheated to 200°C, and cooled to room temperature with the furnace to obtain an alloy ingot. The alloy α+β / β phase transition point is determined to be approximately 961±10°C by combining metallographic method and differential thermal analysis method.
[0092] S3: The titanium-based composite ingot is kept at 100°C above the β phase transformation point for 30 minutes, and then forged once along the X, Y and Z directions with a deformation of 50%;
[0093] S4: the titanium-based composite material after forging is subjected to a solution treatment at 1200°C in the β phase region, and after reaching the set temperature, the temperature is kept for 1 hour, and then cooled to room temperature using 20% by mass salt water;
[0094] 54: The quenched titanium-based composite material is kept at 100°C above the β phase transformation point for 30 minutes, and then stretched once in multiple passes along the X and Y directions, with each deformation amount being 10%; after the stretching is completed, it is cooled to room temperature to obtain a finished titanium-based composite material resistant to 750°C high temperature.
[0095] The titanium-based composite material prepared in this embodiment has a phase composition of alternating arrangement of lamellar α-Ti and β-Ti, precipitation of nano-spherical silicides at grain boundaries, and fibrous TiBw with a high aspect ratio. The lamellar α-Ti phase has a width of 0.15 μm, the nano-spherical silicides are evenly distributed, the size is 100 to 250 nm, and the aspect ratio of the fibrous TiBw is 20:1. The room temperature tensile strength of the titanium-based composite material is 1308.24 MPa, the elongation is 5.78%, the tensile strength at 650°C is 873.76 MPa, the elongation is 28.4%, the tensile strength at 700°C is 694.47 MPa, the elongation is 37.3%, and the tensile strength at 750°C is 597.93 MPa, the elongation is 60.9%.
[0096] Example 3
[0097] A titanium-based composite material resistant to high temperatures of 750°C is composed of the following components by weight percentage: 8% Al, 6% Sn, 8% Zr, 2.5% Mo, 2.5% Nb, 1.5% W, 0.5% Si (particle size controlled at 5 microns), 0.5% B (particle size controlled at 5 microns), and the remainder is Ti and unavoidable impurities.
[0098] The short process preparation method is as follows:
[0099] S1: Weigh each raw material according to the weight percentage of each component;
[0100] S2: Sponge titanium, high-purity aluminum, sponge zirconium, high-purity tin ingots, Al-Mo alloy, Al-Nb alloy, Al-W alloy, pure Si powder and pure B powder are mixed for 30 minutes and added into a vacuum induction suspension furnace. Before smelting, the smelting chamber needs to be evacuated to a vacuum degree of 3×10-3Pa, and then argon gas is introduced with a gas pressure of 100Pa. Then, the smelting is performed at 2000°C, and the average holding time after smelting is 20 minutes. The smelting is repeated 5 times. After the smelting is completed, the alloy liquid needs to be poured into a steel mold preheated to 300°C, and cooled to room temperature with the furnace to obtain an alloy ingot. The alloy α+β / β phase transition point is determined to be approximately 961±10°C by combining metallographic method and differential thermal analysis method.
[0101] S3: The titanium-based composite ingot is kept at 150°C above the β phase transformation point for 60 minutes, and then forged three times along the X, Y and Z directions with a deformation of 50%;
[0102] S4: the titanium-based composite material after forging is subjected to a solution treatment at 1250°C in the β phase region, and after reaching the set temperature, the temperature is kept for 2 hours, and then cooled to room temperature using 25% mass fraction salt water;
[0103] 54: The quenched titanium-based composite material is kept at 150°C above the β phase transformation point for 60 minutes, and then stretched four times in multiple passes along the X and Y directions, with each deformation amount being 30%; after the stretching is completed, it is cooled to room temperature to obtain a finished titanium-based composite material resistant to 750°C high temperature.
[0104] The titanium-based composite material prepared in this embodiment has a phase composition of alternating arrangement of lamellar α-Ti and β-Ti, precipitation of nano-spherical silicides at grain boundaries, and fibrous TiBw with a high aspect ratio. The lamellar α-Ti phase has a width of 0.2 μm, and the nano-spherical silicides are evenly distributed with a size of 50 to 200 nm. The aspect ratio of the fibrous TiBw is 23:1. The room temperature tensile strength of the titanium-based composite material is 1346.71 MPa, and the elongation is 7.24%. The tensile strength at 650°C is 827.35 MPa, and the elongation is 32.8%. The tensile strength at 700°C is 736.65 MPa, and the elongation is 47.3%. The tensile strength at 750°C is 612.67 MPa, and the elongation is 68.6%.
[0105] Table 1 Comparison of finished product performance parameters
[0106]
[0107]
[0108] As can be seen from Table 1 above, in terms of microstructure: the lamellar α-Ti phase width of Example 3 is the largest (0.2 μm), the aspect ratio of the fibrous TiBw is also the largest (23:1), and the nano-spherical silicide has the smallest size and is evenly distributed (50-200 nm), which are conducive to improving the comprehensive performance of the material; in terms of mechanical properties: at room temperature, Example 3 has the highest tensile strength (1346.71 MPa) and the highest elongation (7.24%), showing the best combination of strength and toughness; at high temperatures of 700°C and 750°C, the tensile strength and elongation of Example 3 are both the highest, especially at 750°C, the tensile strength reaches 612.67 MPa and the elongation is 68.6%, showing excellent high temperature performance; at 650°C: although the tensile strength of Example 3 is slightly lower than that of the first two examples, the elongation is the highest, indicating that its plasticity is better; Example 3 shows higher tensile strength and elongation under most test conditions, indicating that it has better comprehensive mechanical properties under high temperature environment.
[0109] Based on the above comprehensive comparison, Example 3 is the best example. It obtains an excellent microstructure by optimizing the alloy composition and heat treatment process, thereby exhibiting optimal mechanical properties at both room temperature and high temperature, and is suitable for the application field of titanium-based composite materials that require high temperature resistance of 750°C, high strength and high plasticity.
[0110] The present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention. In order to make the public have a thorough understanding of the present invention, specific details are described in detail in the following preferred embodiments of the present invention, but those skilled in the art can fully understand the present invention without the description of these details. In addition, in order to avoid unnecessary confusion about the essence of the present invention, well-known methods, processes, procedures, components and circuits are not described in detail.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A titanium-based composite material resistant to high temperatures of 750°C, characterized in that: Including aluminum, tin, zirconium, molybdenum, niobium, tungsten, silicon, boron and titanium; the mass percentage of each component is: Aluminum: 5% to 8%; Tin: 3% to 6%; Zirconium: 5% to 8%; Molybdenum: 1.5% to 2.5%; Niobium: 1.5% to 2.5%; Tungsten: 0.5% to 1.5%; Silicon: 0.2% to 0.5%; Boron: 0.1% to 0.5%; The balance is titanium and unavoidable impurities.
2. The 750°C high temperature resistant titanium-based composite material according to claim 1, characterized in that: The titanium is selected from titanium sponge with a purity of not less than 99.5%; the zirconium is selected from zirconium sponge with a purity of not less than 99.5%; the purity of aluminum, tin, molybdenum, niobium and tungsten is not less than 99.9%.
3. The 750°C high temperature resistant titanium-based composite material according to claim 1, characterized in that: The purity of the silicon is not less than 99.9%, and its particle size is controlled at 1 to 5 microns; the purity of the boron is not less than 99.9%, and its particle size is 1 to 5 microns.
4. A short-process preparation method for a 750°C high-temperature resistant titanium-based composite material, used to prepare the 750°C high-temperature resistant titanium-based composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: weighing the raw materials constituting the titanium-based composite material according to weight percentage, including titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder; S2: after the raw materials are uniformly mixed, they are placed in a vacuum induction suspension melting furnace and smelted under vacuum conditions to obtain an alloy ingot; S3: After heating, the titanium-based alloy ingot is subjected to heat preservation treatment, and then forging is performed in sequence along three directions, namely, X, Y, and Z, so that the ingot undergoes plastic deformation to form a titanium-based composite material of a predetermined shape; S4: subjecting the titanium-based composite material after blank forging to a solid solution treatment at a set temperature, and after heat preservation, placing it in salt water for quenching and cooling; S5: The titanium-based composite material after the solution treatment is heated again to a set temperature and kept warm, and then multiple stretchings are performed along the X and Y directions to obtain a finished titanium-based composite material resistant to high temperatures of 750°C.
5. The short-process preparation method of a 750°C high temperature resistant titanium-based composite material according to claim 4, characterized in that: The S2 specifically includes: S21: adding weighed titanium, aluminum, zirconium, tin, molybdenum, niobium, tungsten, silicon powder and boron powder into a mixing device in proportion, mixing for 20 to 30 minutes, and mixing evenly to form a mixture A; S22: placing the mixture A in a smelting chamber of a vacuum induction suspension furnace, and evacuating the smelting chamber to 3×10-3Pa before smelting; S23: introducing argon gas under vacuum conditions until the pressure reaches 100 Pa, raising the melting temperature to 1900-2000° C., maintaining the melting for 10-20 minutes, and repeating the melting 3-5 times; S24: After smelting, pour the alloy liquid into a steel mold preheated to 200-300°C, and cool to room temperature along with the furnace to obtain an alloy ingot.
6. The short-process preparation method of a 750°C high temperature resistant titanium-based composite material according to claim 4, characterized in that: The S3 specifically includes: S31: heating the alloy ingot to a temperature 100 to 150° C. higher than the β phase transformation point, and keeping the temperature for 30 to 60 minutes; S32: After the heat preservation is completed, the ingot is forged in three directions, X, Y and Z, forging 1 to 3 times, with a deformation amount of 50%; S33: After the multi-directional forging is completed, a titanium-based composite material of a predetermined shape is obtained.
7. The short-process preparation method of a 750°C high temperature resistant titanium-based composite material according to claim 4, characterized in that: The S4 specifically includes: S41: heating the titanium-based composite material after blank forging to a β-phase temperature of 1200-1250° C., and keeping the temperature for 1-2 hours; S42: After the heat preservation is completed, the titanium-based composite material is quickly moved into a 20-25% by mass salt solution for quenching and cooling to room temperature.
8. The short-process preparation method of a 750°C high temperature resistant titanium-based composite material according to claim 4, characterized in that: The S5 specifically includes: S51: heating the solution treated titanium-based composite material to a temperature 100 to 150° C. higher than the β phase transition point, and keeping the temperature for 30 to 60 minutes; S52: After the heat preservation is completed, 1 to 4 stretching passes are performed along the X and Y directions respectively, and the deformation amount each time is 10 to 30%; S53: After the drawing is completed, the product is cooled to room temperature to obtain a finished product of a titanium-based composite material resistant to high temperature of 750°C.